A survey on parasite management by equine veterinarians highlights the need for a regulation change. Issue 2 (14th September 2015) - Sallé, Guillaume; Cabaret, Jacques
Abstract : Introduction: In‐depth knowledge of the use of anthelminthics in the field, especially by veterinarians, is required to design more sustainable parasite control strategies. Materials and methods: An online survey was sent by e‐mail to 940 equine veterinary practitioners to describe their equine practice, their awareness about parasites and the management strategies they apply. Results: Gastrointestinal parasites were generally considered (68%) as an issue of moderate importance. Drug efficacy failure was a minor or moderate issue for 47% and 48% of responders, respectively. Parasite management mostly relied on the use of systematic calendar treatments across a wide variety of horse owners (ie, riding schools, studs or hobby horse owners). Almost half of the practitioners (42%) never performed Faecal Egg Count (FEC) before drenching. Horse owners or their employees in charge of equines were reported to be the only person managing drenching in 59% of the collected answers. This was associated with the report of many off‐label uses of anthelmintics and the frequent buying of drugs using the internet. Conclusions: Given the critical situation regarding anthelmintic resistance, it seems necessary for veterinarians to reclaim parasite management and prevention as a specific topic. Implementation of stricter regulations for use of anthelmintics, like the one applied in Denmark, may make parasitic management in equids more sustainable.